ANALISIS TINGKAT KESEHATAN KOPERASI JASA KEUANGAN SYARIAH - Desfitia Ramadhania; Mediya Destalia; M. Iqbal Harori (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2022)
This study aims to determine the health level of the Islamic Financial Services Cooperative BMT El Ihsan Pringsewu for the 2017-2019 period, in review of the Regulation of the State Minister for Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 35.3/Per/M.KUKM/X/2007. This type of research uses descriptive quantitative. The population and sample in this study are the same, namely the Sharia Financial Services Cooperative BMT El Ihsan Pringsewu. Sources of data in this study using primary data sources and secondary data. The research data collection technique used documentation techniques in the form of archived data on KJKS BMT El Ihsan financial statements and interview techniques with the BMT El Ihsan Sharia Financial Services Cooperative. The results of this study indicate that KJKS BMT El Ihsan Pringsewu in 2017-2019 is included in the healthy category. In 2017 it got an overall score of 88, in 2018 it got an overall score of 91.75, and in 2019 it got an overall score of 93. Based on this score KJKS BMT El Ihsan is included in the predicate of the health level in the healthy category with a score range of 81-100 according to the Ministerial Regulation State Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 35.3/Per/M.KUKM/X/2007. ABSTRAK Penelitian ini bertujuan untuk mengetahui tingkat kesehatan Koperasi Jasa Keuangan Syariah BMT El Ihsan Pringsewu Periode 2017-2019, dalam tinjauan Peraturan Menteri Negara Koperasi dan Usaha Kecil Menengah Republik Indonesia Nomor: 35.3/Per/M.KUKM/X/2007. Jenis penelitian ini menggunakan deskriptif kuantitatif. Populasi dan sampel pada penelitian ini sama yaitu Koperasi Jasa Keuangan Syariah BMT El Ihsan Pringsewu. Sumber data penelitian ini menggunakan sumber data primer dan data sekunder. Teknik pengumpulan data penelitian menggunakan teknik dokumentasi berupa data arsip laporan keuangan KJKS BMT El Ihsan dan teknik wawancara kepada pihak Koperasi Jasa Keuangan Syariah BMT El Ihsan. Hasil penelitian ini menunjukkan bahwa KJKS BMT El Ihsan Pringsewu tahun 2017-2019 termasuk ke dalam kategori sehat. Tahun 2017 memperoleh skor kesuluruhan sebesar 88, tahun 2018 memperoleh skor kesuluruhan sebesar 91,75, dan tahun 2019 memperoleh skor keseluruhan 93. Berdasarkan skor tersebut KJKS BMT El Ihsan termasuk ke dalam predikat tingkat kesehatan kategori sehat dengan rentang skor 81-100 menurut Peraturan Menteri Negara Koperasi dan Usaha Kecil Menengah Republik Indonesia Nomor : 35.3/Per/M.KUKM/X/2007.